EVALUATION OF IN VITRO ANTIOXIDANT ACTIVITY OF A MEDICINAL HERB, WEDELIA CHINENSIS (OSBECK) MERRILL. - H, Rehana Banu; N, Nagarajan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective is to evaluate the antioxidant activity of the methanolic leaf extract of Wedelia chinensis. Methods: In vitro antioxidant activity was evaluated by studying 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, superoxide radical scavenging activity, ferric reducing ability of plasma (FRAP) scavenging activity, hydroxyl radical scavenging activity, metal chelating activity, and total antioxidant activity. Ascorbic acid, BHT, quercetin, and EDTA were used as standards for the experiments. Results: Inhibition concentration50 values observed for DPPH radical scavenging, superoxide radical scavenging, and hydroxyl radical scavenging activities were determined to be 62.5, 769.23, and 617.28 Î¼g/ml, respectively and that of FRAP scavenging, metal chelating, and total antioxidant activities were found to be 343 Î¼mol Fe (II)/g, 79.56 mg EDTA/g extract, and 398.17 mg ascorbic acid eq/g extract, respectively. Conclusion: The results clearly indicate that methanolic leaf extract of the study species W. chinensis is effective in scavenging free radicals and has the potential to be a powerful antioxidant.